Preparation method of high-temperature catalytic filtration silicon carbide ceramic membrane
By adding reinforcement agents such as zirconia and mullite fibers to silicon carbide ceramic materials, and preparing high-temperature catalytic filtering silicon carbide ceramic membranes, the problem of ceramic materials being easily brittle at high temperatures is solved, and the efficient removal of various pollutants is achieved. Effect.
Patent Information
- Application Number
- CN202411584301.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Existing silicon carbide ceramic materials are brittle at high temperatures, and have prominent corrosion resistance and life problems, making it difficult to meet the needs of high-temperature flue gas purification.
High-temperature catalytic filtered silicon carbide ceramic membrane is prepared using silicon carbide micropowder, zirconia, mullite fiber and other materials. By coating the fiber transition layer, dipping the catalyst layer and forming an intermetallic compound layer, the bending strength of the ceramic membrane is improved and Catalytic properties.
It significantly improves the bending strength and catalytic performance of the silicon carbide ceramic film, and can efficiently remove dust, CO2, VOCs, NOx, SO2 and H2S in high-temperature waste gas, and is suitable for a wide range of industrial applications.
Smart Images

Figure CN119456001A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal chemical flue gas pollution control and functional new materials, and relates to a method for preparing a high-temperature catalytic filtering silicon carbide ceramic membrane. Background Art
[0002] In the industrial production processes such as coal chemical industry, waste incineration, cement and metallurgy, biomass gasification, etc., a large amount of high-temperature tail gas with complex components will be generated, accompanied by a large amount of ultrafine particles and VOCs, NOx, SO 2 , CO 2 , H 2 S is a corrosive gas component. Direct discharge will cause serious environmental pollution and must be purified to meet the standards before discharge.
[0003] Silicon carbide porous ceramics can operate for a long time at high temperature (>500℃), and have excellent thermal shock resistance, corrosion resistance, creep resistance, high mechanical strength and other characteristics. They are high-temperature flue gas dust removal materials with broad application prospects. However, silicon carbide ceramics are brittle materials, and their low room temperature strength and poor fracture toughness limit the application range of silicon carbide ceramics. Therefore, the preparation of silicon carbide-based composite ceramics with higher strength and higher fracture toughness has always been one of the main contents of silicon carbide ceramic research.
[0004] Since the technical concept of ceramic filter tube catalyst was proposed, there has been no research report on large-scale industrial production. Researchers in Germany, Italy and South Korea have conducted theoretical and experimental explorations on it, and Germany has already developed related ceramic filter tube catalyst products, while domestic research on this has just started and is still in the experimental exploration stage. For example, the existing public technology: CN201110104548.7 provides a preparation method of silicon carbide porous ceramics that can be used as high-temperature smoke filters. Although the number of pores and specific surface area of silicon carbide porous ceramics can be greatly increased, there are still problems with the brittleness, corrosion resistance and life of ceramics. Summary of the invention
[0005] In order to solve at least one of the above problems, the present invention provides a method for preparing a high-temperature catalytic filtration silicon carbide ceramic membrane, which increases the bending strength of the silicon carbide ceramic membrane, and also provides a method for preparing a high-temperature catalytic filtration silicon carbide ceramic membrane in catalytic degradation of dust, CO in flue gas. 2 、VOCs、NOx、SO 2 , H 2 S and other pollutants.
[0006] In order to achieve the above object, the present invention adopts the following technical means: A first aspect of the present invention provides a method for preparing a high-temperature catalytic filtration silicon carbide ceramic membrane, comprising the following steps: (1) Preparation of silicon carbide ceramic support Silicon carbide micropowder is used as aggregate, zirconium oxide is used as sintering aid, silicon carbide whisker and mullite fiber are used as reinforcing agent, polyvinyl alcohol is used as binder, the raw materials are mechanically mixed, additives are added and mixed quickly to obtain granulated powder, which is formed by cold isostatic pressing machine, dried in an oven at 100-120°C, and sintered at a high temperature of more than 1500°C to obtain a silicon carbide ceramic support; (2) Coating fiber transition layer Mixing mullite fiber, aluminum silicate fiber, activated carbon fiber, polyvinyl alcohol and deionized water into a slurry, uniformly coating the slurry on the surface of the silicon carbide ceramic support in step (1), and drying at 60-80° C. for 2-4 hours to obtain a ceramic support with a fiber transition layer; (3) Dip-coating catalyst layer Mixing a vanadium-molybdenum-cerium-titanium catalyst, sodium tripolyphosphate and polyvinyl alcohol to form a suspension solution, dipping the ceramic support prepared in (2) into the suspension solution, and ultrasonically vibrating the suspension solution for dip coating, and drying in an oven at 100-120° C. to obtain a ceramic support having a catalytic layer; (4) Formation of intermetallic compound layer Silicon carbide powder, iron oxide, aluminum oxide, zirconium oxide, boron oxide and mullite whisker are placed in a mixer, mixed thoroughly and then placed in a heating kettle, heated and melted to form a suspension, and additives are added to prepare a casting liquid, which is then sprayed multiple times on the surface of the ceramic support body that has completed step (3) by rotary thermal spraying, dried in an oven at 100-120°C, and sintered at a high temperature of more than 1200°C to form a ceramic / FeAl intermetallic compound composite coating, thereby obtaining a catalytic filtration silicon carbide ceramic membrane.
[0007] In some embodiments of the present invention, in step (1), the mass percentage of aggregate is 80%-90%, the mass percentage of sintering aid is 5%-10%, the mass percentage of reinforcing agent is 5%-10%, and the mass percentage of binder is 1%-2%.
[0008] The mass percentage of silicon carbide whiskers in the reinforcing agent is 5%, and the mass percentage of mullite fibers is 3%.
[0009] In some embodiments of the present invention, in step (2), the mass percentage of mullite fiber is 2%-10%, the mass percentage of aluminum silicate fiber is 2%-10%, the mass percentage of activated carbon fiber is 5%-10%, the mass percentage of polyvinyl alcohol is 3%-5%, and the mass percentage of deionized water is 60%-80%.
[0010] In some embodiments of the present invention, in step (3), the mass percentage of the catalyst is 8%-12%, the mass percentage of the dispersant is 50%-80%, and the mass percentage of the binder is 5%-10%.
[0011] In some embodiments of the present invention, in step (4), the mass percentage of silicon carbide powder is 20%-30%, the mass percentage of iron oxide is 15%-25%, the mass percentage of aluminum oxide is 15%-25%, the mass percentage of zirconium oxide is 1%-5%, the mass percentage of boron oxide is 1%-5%, and the mass percentage of mullite whiskers is 10%-20%.
[0012] In some embodiments of the present invention, the activated carbon fibers have a length of 100-400 microns.
[0013] In some embodiments of the present invention, the additive is one or more of paraffin wax and polyvinyl alcohol. In some specific embodiments of the present invention, the mass percentage of paraffin wax is 1%-5%, and the mass percentage of polyvinyl alcohol is 1%-5%.
[0014] The second aspect of the present invention provides a catalytic filtration silicon carbide ceramic membrane prepared according to the method described in the first aspect.
[0015] The third aspect of the present invention provides the use of the catalytic filtering silicon carbide ceramic membrane described in the second aspect in catalytic removal of various pollutants in high-temperature exhaust gas.
[0016] In some embodiments of the present invention, the various pollutants in the high temperature exhaust gas include dust, CO 2 、VOCs、NOx、SO 2 and H 2 S.
[0017] Beneficial Effects of the Invention Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adds activated carbon fiber to the fiber transition layer so that its surface has a microporous structure, which can serve as an attachment point for the catalyst and also play a connecting role between the silicon carbide fiber and the catalyst. Therefore, the activated carbon fiber allows the catalyst to be tightly combined with the support, greatly improving the catalyst loading and the firmness of the combination.
[0018] 2. The present invention evenly disperses the catalyst into the fiber layer of the silicon carbide ceramic support by impregnation, which not only ensures the gas permeability and reduces the pressure drop, but also catalyzes the degradation of CO in the flue gas while filtering and removing dust. 2 、VOCs、NOx、SO 2 , H 2 S et al.
[0019] 3. The present invention introduces metals such as iron oxide and aluminum oxide to form a ceramic / FeAl intermetallic compound composite coating, which effectively improves the brittle characteristics of the ceramic membrane, enhances the mechanical properties of the ceramic membrane, and prolongs its service life.
[0020] 4. The catalytic filtration silicon carbide ceramic membrane prepared by the method of the present invention is resistant to high temperatures and corrosion, has a dust removal efficiency of up to 99.9%, can remove a variety of pollutants, can be mass-produced, has reduced costs, is suitable for a wide temperature range, has a long service life, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The figure shows the comparison of the bending strength of the materials prepared in Examples 1-2 of the present invention and Comparative Examples 1-2; Figure 2 The catalytic removal effects of the materials prepared by Examples 1-2 of the present invention and Comparative Examples 1-2 on various pollutants are compared. DETAILED DESCRIPTION
[0022] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, and the materials cited herein and those cited by them are incorporated by reference. Those skilled in the art will recognize or will learn through routine experimentation that there are many equivalents to the specific embodiments of the invention described herein. Such equivalents are intended to be encompassed by the claims.
[0024] A method for preparing a high-temperature catalytic filtration silicon carbide ceramic membrane comprises the following steps: (1) Preparation of silicon carbide ceramic support Silicon carbide micropowder is used as aggregate, zirconium oxide is used as sintering aid, silicon carbide whisker and mullite fiber are used as reinforcing agents, and polyvinyl alcohol is used as binder. The raw materials are mechanically mixed, and then additives are added and quickly mixed to obtain granulated powder, which is formed by a cold isostatic press, dried in an oven at 100-120°C, and sintered at a high temperature of more than 1500°C to obtain a silicon carbide ceramic support body; wherein the mass percentage of the aggregate is 80%-90%, the mass percentage of the sintering aid is 5%-10%, the mass percentage of the reinforcing agent is 5%-10%, the mass percentage of the binder is 1%-2%, the mass percentage of the silicon carbide whisker in the reinforcing agent is 5%, and the mass percentage of the mullite fiber is 3%; and the additive is 1%-5% paraffin wax.
[0025] (2) Coating fiber transition layer Mullite fiber, aluminum silicate fiber, activated carbon fiber, polyvinyl alcohol and deionized water are mixed into a slurry, and the slurry is evenly coated on the surface of the silicon carbide ceramic support in step (1), and dried at 60-80° C. for 2-4 hours to obtain a ceramic support with a fiber transition layer; wherein the mass percentage of mullite fiber is 2%-10%, the mass percentage of aluminum silicate fiber is 2%-10%, the mass percentage of activated carbon fiber is 5%-10%, the mass percentage of polyvinyl alcohol is 3%-5%, and the mass percentage of deionized water is 60%-80%; and the length of the activated carbon fiber is 100-400 μm.
[0026] (3) Dip-coating catalyst layer A vanadium-molybdenum-cerium-titanium catalyst, a dispersant sodium tripolyphosphate, and a binder polyvinyl alcohol are mixed to form a suspension solution, and the ceramic support prepared in (2) is immersed in the suspension solution, and the suspension solution is ultrasonically vibrated for dip coating, and then dried in an oven at 100-120°C to obtain a ceramic support having a catalytic layer; wherein the mass percentage of the vanadium-molybdenum-cerium-titanium catalyst is 8%-12%, the mass percentage of the dispersant sodium tripolyphosphate is 50%-80%, and the mass percentage of the binder polyvinyl alcohol is 5%-10%.
[0027] (4) Formation of intermetallic compound layer Put silicon carbide powder, iron oxide, aluminum oxide, zirconium oxide, boron oxide and mullite whisker into a mixer, mix them thoroughly and then put them into a heating kettle, heat and melt them to form a suspension, add additives to prepare a casting liquid, and spray them on the surface of the ceramic support body after completing step (3) by rotary thermal spraying for multiple times, dry them in an oven at 100-120°C, and sinter them at a high temperature of more than 1200°C to form a ceramic / FeAl intermetallic compound composite coating, so as to obtain a catalytic filtration silicon carbide ceramic membrane. Among them, the mass percentage of silicon carbide powder is 20%-30%, the mass percentage of iron oxide is 15%-25%, the mass percentage of aluminum oxide is 15%-25%, the mass percentage of zirconium oxide is 1%-5%, the mass percentage of boron oxide is 1%-5%, the mass percentage of mullite whisker is 10%-20%, and the additives are 1%-5% paraffin wax and 1%-5% polyvinyl alcohol.
[0028] The present invention also provides a catalytic filtering silicon carbide ceramic membrane prepared according to the method described above.
[0029] The present invention also provides the use of the catalytic filtration silicon carbide ceramic membrane described above in catalytic removal of various pollutants in high-temperature exhaust gas; the various pollutants in high-temperature exhaust gas include dust, CO 2 、VOCs、NOx、SO 2 and H 2 S.
[0030] The technical solution of the present application is further described in detail below in conjunction with specific implementation plans.
[0031] Example 1 (1) Preparation of silicon carbide ceramic support Silicon carbide powder is used as aggregate, zirconium oxide is used as sintering aid, silicon carbide whisker and mullite fiber are used as reinforcing agents, polyvinyl alcohol is used as binder, and paraffin is used as additive, wherein the mass percentages of aggregate, sintering aid, reinforcing agent and binder are 85%, 5%, 8% and 2% respectively, the mass percentage of silicon carbide whisker in the reinforcing agent is 5%, and the mass percentage of mullite fiber is 3%. After mechanical mixing, 3% by mass of paraffin is added and mixed quickly to obtain granulated powder, which is then formed, dried in an oven at 105°C, and sintered in an air atmosphere muffle furnace at 1600°C to obtain a silicon carbide ceramic membrane support.
[0032] (2) Coating fiber transition layer Mullite fiber, aluminum silicate fiber, activated carbon fiber with a length of 300 microns, polyvinyl alcohol, and deionized water are used as raw materials. The mass percentages of each raw material are 2%, 2%, 5%, 3%, and 80%, respectively. Mix and stir evenly. Mix the mixed slurry with zirconium oxide balls at a mass ratio of 1:1.5 and put them into a ball mill. Mill at a speed of 200 rpm for half an hour to obtain a mixed uniform slurry, and add silicon carbide powder.
[0033] The fiber transition layer is uniformly coated on the surface of the silicon carbide ceramic membrane support body by a spin coating method to form a fiber transition layer, dried in an oven at 80°C, and sintered in a muffle furnace at 1300°C to obtain a fiber transition layer.
[0034] (3) Dip-coating catalyst layer A vanadium-molybdenum-cerium-titanium catalyst, sodium tripolyphosphate and polyvinyl alcohol are mixed in a slurry at a mass percentage of 10%, 70% and 10%, and the ceramic support prepared in step (2) is immersed in the suspension. The silicon carbide ceramic membrane is ultrasonically immersed for 1 hour, dried in an oven at 105°C, and sintered in a muffle furnace at 600°C to obtain a ceramic support with a catalyst layer.
[0035] (4) Intermetallic compound layer Silicon carbide powder, iron oxide, aluminum oxide, zirconium oxide, boron oxide and mullite whisker are put into a mixer in a ratio of 20%, 30%, 28%, 7%, 5% and 10% by mass, mixed thoroughly and put into a heating kettle, heated and melted to form a suspension, and 3% by mass of polyvinyl alcohol and 1% by mass of paraffin are added to prepare a casting liquid, which is sprayed on the surface of a ceramic support coated with a transition layer catalyst layer by rotary thermal spraying for multiple times, dried in an oven at 105°C, and sintered in a muffle furnace at 1300°C to form a ceramic / FeAl intermetallic compound composite coating to obtain a catalytic filtration silicon carbide ceramic membrane.
[0036] Example 2 The steps are the same as those in Example 1, except that in step (2), the length of the activated carbon fiber is 200 μm.
[0037] Comparative Example 1 The steps are the same as steps (1), (2) and (4) in Example 1, except that there is no step (3) and no catalytic layer is applied.
[0038] Comparative Example 2 The steps are the same as those in Example 1, except that in step (2), iron oxide and aluminum oxide are not added, and there is no FeAl intermetallic compound layer.
[0039] Performance Testing 1. Physical performance test The catalytic filtration silicon carbide ceramic membranes obtained in Example 1 and Comparative Examples 1 to 3 were tested for porosity, pore size, air flux, and compressive and flexural strength. The results are shown in Table 1. The flexural strength is shown in Table 1. Figure 1 shown.
[0040] Table 1 Physical properties of catalytic filtration silicon carbide ceramic membrane
[0041] The results show that after adding iron oxide and aluminum oxide, the bending strength of the prepared catalytic filtration silicon carbide ceramic membrane is greatly increased.
[0042] 2. Dust removal performance and pollutant catalytic degradation performance test Take a 36 mm diameter disk of the silicon carbide ceramic membrane obtained in Examples 1 and 2 and Comparative Examples 1 and 2, respectively, and place it in a reactor at a reaction temperature of 300°C, a toluene concentration of 100 ppm, a NOx concentration of 500 ppm, and a SO 2 Concentration 100 ppm, CO 2 Concentration 500 ppm, H 2 The S concentration was 100 ppm, nitrogen and oxygen were introduced, the oxygen content was 11%, and the total gas flow rate was 1000 ml / min to test its catalytic degradation performance; the dust filtration efficiency test was carried out in accordance with the standard ISO 11057, using a filtration simulation test device, and the test results are shown in Table 2 and Figure 2 shown.
[0043] Table 2 Removal efficiency of silicon carbide ceramic membrane for dust and various pollutants
[0044] The results show that during the preparation of catalytic filtration silicon carbide ceramic membrane, without dipping the catalyst layer, the toluene, NOx, SO 2、 CO 2 and H 2 The removal efficiency of S is greatly reduced, and the catalytic degradation performance of pollutants is reduced during dust removal and filtration.
[0045] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as references separately. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined in the present application.
Claims
1. A method for preparing a high-temperature catalytic filtration silicon carbide ceramic membrane, characterized in that: The steps include: (1) Preparation of silicon carbide ceramic support Silicon carbide micropowder is used as aggregate, zirconium oxide is used as sintering aid, silicon carbide whisker and mullite fiber are used as reinforcing agent, polyvinyl alcohol is used as binder, the raw materials are mechanically mixed, additives are added and mixed quickly to obtain granulated powder, which is formed by cold isostatic pressing machine, dried in an oven at 100-120°C, and sintered at a high temperature of more than 1500°C to obtain a silicon carbide ceramic support; (2) Coating fiber transition layer Mixing mullite fiber, aluminum silicate fiber, activated carbon fiber, polyvinyl alcohol and deionized water into a slurry, uniformly coating the slurry on the surface of the silicon carbide ceramic support in step (1), and drying at 60-80° C. for 2-4 hours to obtain a ceramic support with a fiber transition layer; (3) Dip-coating catalyst layer A vanadium-molybdenum-cerium-titanium catalyst, a dispersant sodium tripolyphosphate, and a binder polyvinyl alcohol are mixed to form a suspension solution, the ceramic support prepared in (2) is immersed in the suspension solution, and the suspension solution is ultrasonically vibrated for dip coating, and then dried in an oven at 100-120° C. to obtain a ceramic support having a catalytic layer; (4) Formation of intermetallic compound layer Silicon carbide powder, iron oxide, aluminum oxide, zirconium oxide, boron oxide and mullite whisker are placed in a mixer, mixed thoroughly and then placed in a heating kettle, heated and melted to form a suspension, and additives are added to prepare a casting liquid, which is then sprayed multiple times on the surface of the ceramic support body that has completed step (3) by rotary thermal spraying, dried in an oven at 100-120°C, and sintered at a high temperature of more than 1200°C to form a ceramic / FeAl intermetallic compound composite coating, thereby obtaining a catalytic filtration silicon carbide ceramic membrane.
2. The preparation method according to claim 1, characterized in that: In the step (1), the mass percentage of aggregate is 80%-90%, the mass percentage of sintering aid is 5%-10%, the mass percentage of reinforcing agent is 5%-10%, the mass percentage of binder is 1%-2%, the mass percentage of silicon carbide whisker in the reinforcing agent is 5%, and the mass percentage of mullite fiber is 3%.
3. The preparation method according to claim 1, characterized in that: In the step (2), the mass percentage of mullite fiber is 2%-10%, the mass percentage of aluminum silicate fiber is 2%-10%, the mass percentage of activated carbon fiber is 5%-10%, the mass percentage of polyvinyl alcohol is 3%-5%, and the mass percentage of deionized water is 60%-80%.
4. The preparation method according to claim 1, characterized in that: In the step (3), the mass percentage of the catalyst is 8%-12%, the mass percentage of the dispersant sodium tripolyphosphate is 50%-80%, and the mass percentage of the binder polyvinyl alcohol is 5%-10%.
5. The preparation method according to claim 1, characterized in that: In the step (4), the mass percentage of silicon carbide powder is 20%-30%, the mass percentage of iron oxide is 15%-25%, the mass percentage of aluminum oxide is 15%-25%, the mass percentage of zirconium oxide is 1%-5%, the mass percentage of boron oxide is 1%-5%, and the mass percentage of mullite whiskers is 10%-20%.
6. The preparation method according to claim 1, characterized in that: The length of the activated carbon fiber is 100-400 microns.
7. The preparation method according to claim 1, characterized in that: The additive is one or more of paraffin and polyvinyl alcohol.
8. A catalytic filtration silicon carbide ceramic membrane prepared according to the method according to any one of claims 1 to 7.
9. Use of the catalytic filtration silicon carbide ceramic membrane according to claim 8 in catalytic removal of various pollutants in high-temperature exhaust gas.
10. The use according to claim 9, characterized in that: The various pollutants in high-temperature exhaust gas include dust, CO2, VOCs, NOx, SO2 and H2S.
Citation Information
Patent Citations
Preparation method of silicon carbide porous ceramic capable of serving as high-temperature smoke dust filter
CN102219543A
Technique for preparing liquid phase sintering silicon carbide ceramic
CN101077838A
Coating type catalyst composition, catalytic filter tube and preparation method thereof
CN113426438A
Mullite fiber reinforced silicon carbide ceramic filter tube and preparation method thereof
CN113651633A
Synchronous removal of NOx and VOCs (Volatile Organic Compounds) and preparation process thereof
CN114950010A